Bank Soundness and Internal Factors Influencing Profitability: Evidence From Bank Muamalat Indonesia - Ahmad Fatoni; Muhamad Nadratuzzaman Hosen; Rahmawati Rahmawati; Kurnia Dwi Sari Utami (FEB Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the health of Bank Muamalat Indonesia and examine the effect of internal factors on the bank's profitability. The bank health analysis was conducted using the CAMEL, RGEC, and Altman Z-Score approaches for the 2020-2024 period, while the analysis of the influence of internal factors on profitability used the Autoregressive Distributed Lag (ARDL) model with quarterly time series data for the 2017-2024 period, where Return on Assets (ROA) is used as the dependent variable and Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), and Non-Performing Financing (NPF) as independent variables. The results of the bank health analysis show that Bank Muamalat Indonesia is in a strong and stable financial condition, with relatively stable capital, liquidity, and financing risk, as well as a Z-Score that is consistently in the safe zone, although its profitability performance is still relatively low. The ARDL estimation results show that FDR has a negative effect in the short term but a significant positive effect in the long term on ROA, while CAR, BOPO, and NPF have a significant negative effect on ROA. These findings indicate that although Bank Muamalat has strong financial stability, increasing profitability is highly dependent on optimizing intermediation functions, improving operational efficiency, and managing financing quality.